Reliability of the multipeg™ transducer in measuring dental implant stability by using a resonance frequency analysis device (Osstell®): An observational clinical study - Dhahi, Alamin Y; Bede, Salwan Y; Khachadourian, Haig (Journal of Baghdad College of Dentistry, 2023)
Background: Measuring implant stability is an important issue in predicting treatment success. Dental implant stability is usually measured through resonance frequency analysis (RFA). Osstell® RFA devices can be used with transducers (Smartpeg™) that correspond to the implants used as well as with transducers designed for application with Penguin® RFA devices (Multipeg™). Aims: This study aims to assess the reliability of a MultiPeg™ transducer with an Osstell® device in measuring dental implant stability. Materials and Methods: Sixteen healthy participants who required dental implant treatment were enrolled in this study. Implant stability was measured by using an Osstell® device with two transducers, namely, Smartpeg™ and Multipeg™. Insertion torque was also measured and recorded as >50 and ≤50 N·cm. Unpaired t-test and Mann–Whitney U test were conducted to assess the relationships of the implant stability values obtained by the two transducers with insertion torque, whereas Pearson and Spearman’s correlations were utilized to investigate correlations between the two transducers. Interclass correlation coefficients were applied to assess the reliability between the two transducers. Results: Implant stability measurements (primary and secondary) showed strong positive correlations between Smartpeg™ and Multipeg™. The reliability values between both transducers in primary and secondary implant stability measurements were 0.922 and 0.981, respectively. The use of both transducers revealed higher implant stability measurements for implants inserted with insertion torque > 50 N·cm than those inserted with insertion torque ≤ 50 N·cm. Conclusions: This study demonstrated that the Multipeg™ transducer is reliable in measuring the stability of dental implants using an Osstell® device.